Enfoques de investigación en problemas verbales aritméticos aditivos - Castro Martínez, E.; Rico Romero, Luis; Gil Cuadra, Francisco (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A main field in the current research in Mathematics Education is the work with arithmetical word problem solving, which is both interesting and useful. There is ample previous work on this topic and it has received a very systematic treatment from different focuses. Researchers getting involved in this field need to know previous works and current focuses to clarify their research goals. In this study we offer a review about previous research done on difficulties with arithmetical word problems.